Astilbin from Smilax glabra Roxb. alleviates high-fat diet-induced metabolic dysfunction. Issue 9 (7th April 2022) - Wang, Tingwei; Ye, Yongli; Ji, Jian; Zhang, Shuang; Yang, Xingxing; Xu, Jiayuan; Wang, Jia-Sheng; Chen, Zhiyuan; Xia, Bangen; Shen, Hongfang; Xia, Ruowei; Shi, Wenqin; et al.
Abstract : Astilbin caused a significant improvement in lipid metabolism in HFD-fed mice. Astilbin could reduce weight gainand insulin resistance in obese individuals and modify intestinal microbiota disorders, lipid metabolism, and xanthine metabolism. Abstract : Overweight, obesity, and related diseases are currently the major public health problems worldwide. Astilbin, extracted from the rhizome of Smilax glabra Roxb., is known to have significant anti-inflammatory activity and hepatoprotective effect. Studies have shown that it can inhibit adipogenesis in adipocytes in vitro ; however, the intervention benefits of astilbin against obesity and related diseases along with its associated mechanisms remain unknown. This study aimed to demonstrate the impact of astilbin consumption on the overall biochemical pattern of high-fat diet (HFD) mice by using a combined multi-omics approach. Our data indicated that astilbin reduced body weight, insulin resistance, and inflammation in mice fed an HFD. Astilbin improved HFD-induced gut microbial dysbiosis by decreasing the Firmicutes-to-Bacteroidetes ratio, by increasing beneficial bacteria such as Alistipes and Muribaculum and decreasing harmful bacteria including Lachnospiraceae FCS020 group, Coriobacteriaceae UCG-002, and Lachnospiraceae UCG-008, resulting in enhanced intestinal carbohydrate and lipid metabolism. Meanwhile, astilbin protected the integrity of the intestinal barrier in HFD mice, increased short-chain fatty acid levels, and reduced metabolic endotoxemia. We further showed that astilbin attenuated hepatic lipid droplet aggregation and triglyceride accumulation in HFD mice, affected glutamate metabolism-related pathways, and enhanced hepatic ATP transduction pathways and attenuated xanthine metabolism pathways in mice, which were positively correlated with the abundance of Alistipes and negatively correlated with Ruminococcaceae UCG-003 . The results highlighted that astilbin could be used as a prebiotic for the prevention of "gut–liver axis" damage and metabolic disruption in obese individuals.